Strategi Membangun Loyalitas Pegawai dan Optimalisasi Kinerja Sumber Daya Manusia (SDM) di Moderamen GBKP Kabanjahe - Anisa Sitepu; Frans Antoni Sihite; Benni Purba; Menanti Br Sembiring (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze strategies for building employee loyalty and optimizing human resource performance at Moderamen GBKP Kabanjahe. Employee loyalty plays an important role in maintaining organizational stability, increasing work commitment, and supporting the achievement of institutional goals. In a service-based organization, loyalty is influenced not only by material factors but also by service values, responsibility, and the family-oriented culture developed within the organization.This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving informants such as the General Secretary, division leaders, and staff members at Moderamen GBKP Kabanjahe. The collected data were analyzed through data reduction, data display, and conclusion drawing..The results indicate that strategies to build employee loyalty are implemented through the application of a family-oriented culture, the internalization of spiritual service values, participative and open leadership, and effective communication. The optimization of human resource performance is achieved through clear task distribution, spiritual development, and routine work coordination. However, several challenges remain, including the lack of a structured performance evaluation system and the potential subjectivity arising from overly personal working relationships. Therefore, strengthening a more objective performance evaluation system is necessary without eliminating the family values that characterize the organization.This study is expected to serve as an evaluation reference and provide input for Moderamen GBKP Kabanjahe in improving employee loyalty and human resource performance sustainably.